2005
DOI: 10.1016/j.cell.2005.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Lysine 48-Linked Ubiquitin-Chain Synthesis by the Cullin-RING Ubiquitin-Ligase Complex SCF-Cdc34

Abstract: Ubiquitin chains linked via lysine 48 (K48) of ubiquitin mediate recognition of ubiquitinated proteins by the proteasome. However, the mechanisms underlying polymerization of this targeting signal on a substrate are unknown. Here we dissect this process using the cyclin-dependent kinase inhibitor Sic1 and its ubiquitination by the cullin-RING ubiquitin ligase SCF(Cdc4) and the ubiquitin-conjugating enzyme Cdc34. We show that Sic1 ubiquitination can be separated into two steps: attachment of the first ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
343
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(362 citation statements)
references
References 31 publications
17
343
1
1
Order By: Relevance
“…It had been presumed that polyubiquitin chains are formed by conjugating ubiquitin moieties, one at a time, first to a lysine residue in a substrate, and then to a lysine in the previously-attached ubiquitin molecule. This appears to be the case for some E2s (13)(14)(15). However, we and several other groups recently found that ubiquitin chains can also be preassembled on the catalytic cysteine of the E2 enzyme Ube2g2 and its yeast homologue Ubc7p both in vitro and in vivo (16)(17)(18)(19).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…It had been presumed that polyubiquitin chains are formed by conjugating ubiquitin moieties, one at a time, first to a lysine residue in a substrate, and then to a lysine in the previously-attached ubiquitin molecule. This appears to be the case for some E2s (13)(14)(15). However, we and several other groups recently found that ubiquitin chains can also be preassembled on the catalytic cysteine of the E2 enzyme Ube2g2 and its yeast homologue Ubc7p both in vitro and in vivo (16)(17)(18)(19).…”
mentioning
confidence: 65%
“…This was caused by the transfer of Flag-UbK48R to free ubiquitin present in the reaction. The formation of such a diubiquitin species has been used as an indicator of ligase activity for some RING E3s, and the amount of diubiquitin generated depends on the concentration of the ubiquitin acceptor (13,27). Indeed, when the Ube2g2ϳFlag-UbK48R thioester was incubated with excess ubiquitin, gp78C⌬L could generate diubiquitin more efficiently than wild-type gp78C (Fig.…”
Section: Results Gp78 Contains 2 Oligomerization Sites One Of Which mentioning
confidence: 99%
“…Although the activation of the intrinsic activity of a CRL is one mode of regulation by neddylation, it is not the only one. Indeed, CRL neddylation can block association with the CAND1 exchange factor and enhance association with the CSN complex, as described in detail below.In the on state, CRLs can be highly processive, giving rise to multiple catalytic cycles before substrate dissociation [70][71][72]. This feature has much to do with how a CRL-specific, ubiquitinchain-forming E2 associates with the cullin-RING E3 scaffold.…”
mentioning
confidence: 99%
“…Ubc1 cannot be recharged by E1 in this assay due to inactivation of E1 and free E2, and thus the assay measures a single turnover of E2, allowing estimates of Ubc1 catalytic rate and affinity for acceptor ubiquitin (3,18).…”
Section: Resultsmentioning
confidence: 99%
“…Cloning, Expression, and Purification of Proteins-To make 32 P-labeled K48R mutant ubiquitin for diubiquitin synthesis assays, GST-TEV-PKA-K48R-ubiquitin (a gift from Ray Deshaies (18)) was expressed in Escherichia coli, radioactively labeled, and purified as described (3). E2 constructs, including Ubc1-His 6 , Ubc1⌬UBA-His 6 , Ubc4-His 6 , and Ubc4-UBA-His 6 , were expressed in E. coli and purified as described (4).…”
Section: Methodsmentioning
confidence: 99%